Design methodology of high‐power and high‐efficiency composite amplifiers. Issue 7 (26th April 2013) - Djukanovic, Milena; Piattella, Luca; Roberto, Natalino; Tommasino, Pasquale; Trifiletti, Alessandro
Abstract A methodology to design high‐power amplifiers composed of several amplifier blocks and passive combiners/dividers is proposed.The optimum matching condition between amplifiers and combiners has been found using the mixed‐mode S‐parameters approach. Measurements and computer‐aided design simulations have been successfully used to validate the proposed approach. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1500–1504, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27600